2005
DOI: 10.1074/jbc.m411413200
|View full text |Cite
|
Sign up to set email alerts
|

Mnt1p and Mnt2p of Candida albicans Are Partially Redundant α-1,2-Mannosyltransferases That Participate in O-Linked Mannosylation and Are Required for Adhesion and Virulence

Abstract: The MNT1 gene of the human fungal pathogen Candida albicans is involved in O-glycosylation of cell wall and secreted proteins and is important for adherence of C. albicans to host surfaces and for virulence. Here we describe the molecular analysis of CaMNT2, a second member of the MNT1-like gene family in C. albicans. Candida albicans is the major fungal pathogen of humans. This opportunistic pathogen can cause irritating superficial infections of the mucosa and serious life threatening systemic infections in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
185
2
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(205 citation statements)
references
References 59 publications
17
185
2
1
Order By: Relevance
“…The O-linked oligosaccharides, attached to serine or threonine, consist of a linear chain of one to five ␣1,2-linked mannose residues (12)(13)(14) and are known to be required for full virulence (14). The process of N-glycosylation has been studied extensively in Saccharomyces cerevisiae.…”
mentioning
confidence: 99%
“…The O-linked oligosaccharides, attached to serine or threonine, consist of a linear chain of one to five ␣1,2-linked mannose residues (12)(13)(14) and are known to be required for full virulence (14). The process of N-glycosylation has been studied extensively in Saccharomyces cerevisiae.…”
mentioning
confidence: 99%
“…Mannosyltransferases (och1 and mnt1) could be putatively related to the O-linked mannosylation of proteins, as observed in C. albicans. C. albicans mutants to either mnt1 or och1 showed hypersensitivity to cell wall perturbing agents, suggesting the proteins role in the cell wall maintenance [43,44]. Moreover, a novel transcript encoding to guanosine diphosphatase (gmd1) was detected during the dimorphic transition, whose product is known to regulate mannosylation of Nand O-linked oligosaccharides in Golgi complex [45].…”
Section: Est Processing Pipeline and Annotationmentioning
confidence: 98%
“…The cns1 product is an essential component of the HSP90 complex, which is induced in heat shock response [40]. Mannosyltransferases (mnt1 and och1) orthologues are required for cell wall integrity/virulence and adhesion/virulence, respectively, in C. albicans [43,44]. In S. pombe, the mde10 product is essential for development of spore envelopes [52] evidencing its importance during differentiation process in the cell.…”
Section: Est Processing Pipeline and Annotationmentioning
confidence: 99%
“…These studies indicated that some mannooligosaccharide side chains are correlated with the pathogenicity of the C. albicans cells. 7,24) However, there is no study for the substrate specificity of these enzymes especially for the C. albicans specific mannosyltransferases. To characterize these mannosyltransferases, we need to use the purified recombinant enzyme.…”
Section: Mana1→2mana1→3mana1→3mana1→2mana1→2manmentioning
confidence: 99%